1997
DOI: 10.1093/hmg/6.7.1169
|View full text |Cite
|
Sign up to set email alerts
|

Germline mutations of the MEN1 gene in familial multiple endocrine neoplasia type 1 and related states

Abstract: Familial multiple endocrine neoplasia type 1 (FMEN1) is an autosomal dominant trait characterized by tumors of the parathyroids, gastro-intestinal endocrine tissue, anterior pituitary and other tissues. We recently cloned the MEN1 gene and confirmed its identity by finding mutations in FMEN1. We have now extended our mutation analysis to 34 more unrelated FMEN1 probands and to two related states, sporadic MEN1 and familial hyperparathyroidism. There was a high prevalence of heterozygous germline MEN1 mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
266
8
7

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 433 publications
(310 citation statements)
references
References 19 publications
28
266
8
7
Order By: Relevance
“…This was contradictory to the previous report showing that no mutation of the MEN1 gene was detected in 5 probands with FHP in the United States and Canada [10]. On the other hand, it has recently been reported that a Japanese patient with FHP had a germline mutation of the MEN1 gene (Y353X in exon 8), although the clinical evaluation for MEN1 was not described in this family [13].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This was contradictory to the previous report showing that no mutation of the MEN1 gene was detected in 5 probands with FHP in the United States and Canada [10]. On the other hand, it has recently been reported that a Japanese patient with FHP had a germline mutation of the MEN1 gene (Y353X in exon 8), although the clinical evaluation for MEN1 was not described in this family [13].…”
Section: Discussioncontrasting
confidence: 99%
“…This gene contains 10 exons and encodes a 610 amino acid protein [9]. It has been reported that germline heterozygous mutations of the MEN1 gene are closely related to the endocrine tumorigenesis in MEN1 [10,11]. If a germline mutation of the MEN1 gene was found in a FHP …”
Section: Familial Primary Hyperparathyroidismmentioning
confidence: 99%
“…Each patient met clinical criteria for MEN1 6 and had a MEN1 germline mutation 16 (Table 1). Endocrine and mesenchymal MEN1 tumor manifestations included multiple parathyroid tumors, gastrinomas and metastases, pancreatic neuroendocrine tumors, lung carcinoids, lipomas, and angiofibromas.…”
Section: Patients and Tumorsmentioning
confidence: 99%
“…1 Menin interacts with a wide number of proteins involved in transcriptional regulation, genome stability, cell division, and proliferation. 2 Germline mutations of the MEN1 gene along with the loss of heterozygosity (LOH) result in menin structural changes and subsequent loss of tumor-suppressing function. 3 As for many other tumor suppressor genes, there is no genotype-phenotype correlation in MEN1.…”
Section: Introductionmentioning
confidence: 99%